2013
DOI: 10.1111/nure.12077
|View full text |Cite
|
Sign up to set email alerts
|

Nutritional modulation of cataract

Abstract: Lens opacification or cataract reduces vision in over 80 million people worldwide and blinds 18 million. These numbers will increase dramatically as both the size of the elderly demographic and the number of those with carbohydrate metabolism-related problems increase. Preventative measures for cataract are critical because the availability of cataract surgery in much of the world is insuficient. Epidemiologic literature suggests that the risk of cataract can be diminished by diets that are optimized for vitam… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
63
0
2

Year Published

2015
2015
2022
2022

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 109 publications
(85 citation statements)
references
References 104 publications
(257 reference statements)
2
63
0
2
Order By: Relevance
“…It is estimated that cataracts account for 39% of the world's 37 million blind individuals [7]. Although the real etiology of cataracts remains inconclusive, to date, many factors have been identified to be associated with the risk of cataracts [8,9].…”
Section: Introductionmentioning
confidence: 99%
“…It is estimated that cataracts account for 39% of the world's 37 million blind individuals [7]. Although the real etiology of cataracts remains inconclusive, to date, many factors have been identified to be associated with the risk of cataracts [8,9].…”
Section: Introductionmentioning
confidence: 99%
“…In contrast, if they are benign enough merely to increase susceptibility to environmental insults, including hyperglycemic and dietary (Weikel et al, 2014), ultraviolet light (Taylor et al, 1988), or oxidative (Brennan et al, 2012; Truscott, 2005) damage, they would tend to contribute to age related cataract (Hejtmancik and Smaoui, 2003; Shiels and Hejtmancik, 2007) by exacerbating the accumulation of damage seen to long lived lens proteins with aging (Truscott and Friedrich, 2016). Consistent with these proposed mechanisms, hereditary congenital cataracts are most often transmitted in a highly penetrant Mendelian fashion, and cataracts with a later origin, including progressive and age-related cataracts, are often multifactorial, with contributions from multiple genes providing from 35% to as much as 58% of the risk (McCarty and Taylor, 2001) as well as environmental insults.…”
Section: Introductionmentioning
confidence: 99%
“…While it has been suggested that fatty acids in the diet do not influence the lipid composition of the lens (Nealon et al, 2008), both sterols and flavonoids in the diet can prevent or even reverse cataract in animal and ex vivo human models (Weikel et al, 2014). One of the impacts of modern –omics is that investigators are returning to a close examination of the metabolome, the summation of all the known physiological pathways as well as pathways of the organism’s associated microbiota.…”
Section: Lens Protein Modificationsmentioning
confidence: 99%
“…A review on the nutritional modulation of cataracts appeared in 2014 (Weikel et al, 2014), which focused on familiar dietary components. This current review examines recent exciting developments in sterol-based small molecule biochemistry in the lens and what led to these findings in order to focus attention on the opportunity to deliver small molecules to prevent and treat lens cataract.…”
Section: Introductionmentioning
confidence: 99%